DEVELOPING SITE-SPECIFIC ALLOMETRIC EQUATIONS FOR ABOVE-GROUND BIOMASS ESTIMATION IN PEAT SWAMP FORESTS OF ROKAN HILIR DISTRICT, RIAU PROVINCE, INDONESIA - Nugroho, Nunung Puji (Indonesian Journal of Forestry Research, 2014)
In forest biomass assessment studies, the selection or development of reliable allometric biomass equations is an essential step which determines largely the accuracy of the resulted biomass estimates. Unfortunately, only few studies on allometric biomass equations have been conducted for peat swamp forests and the results are usually not publicly accessible or well documented. Thus, the objective of this study was to develop site-specific allometric equations for above-ground biomass (AGB) estimations in tropical peat swamp forests in Indonesia. These equations were developed based on 51 destructively sampled trees. The results indicated that the developed site-specific allometric equations have coefficient of determination (R2) greater than 95%. The R2 values ranged from 97.0% to 98.7%, where the lowest R2 value resulted from the simplest model which used only DBH as a predictor. Model 5, which used DBH, H and Ï as predictive variables, provided best performance when estimating the AGB of the study area. Hence, as long as reliable data are available as input, Model 5 is recommended. The accuracy and applicability of the allometric equations for peat swamp forests could be improved further by adding more sampled trees from different tree species and/or with a wider DBH range. Considering the importance of wood density in the estimation of the AGB and the lack of this information for peat swamp forest tree species, research should be dedicated to analysing the wood density of the dominant tree species comprising the majority of the AGB density in the study area.